Malino Highland Tea Plantation as a Tourist Destination in Gowa - Parham Taufik (Gudang Jurnal Multidisiplin Ilmu, 2026)
This study aims to determine: (1) The socio-cultural impacts that occur in the Malino Highland tourist area (2) Public perception of the existence of Malino Highland tourism (3) Marketing strategies carried out by the management of the Malino Highland tea plantation. In this study, a qualitative research type was used which was analyzed and written descriptively. Data collection techniques were carried out using observation, interview, and documentation methods involving 10 (ten) informants. Based on the results of the study, it shows that: (1) The intensity and actors of interaction influence the differences in these impacts, from those leading to changes in people's views on foreign cultures, changes in social values ​​in local communities to learning about local culture by tourists. This triggers the emergence of both positive and negative impacts on both parties. (2) Local communities have an equally important position as one of the stakeholders in tourism development, in addition to the government and private industry. (3) The marketing strategy carried out by the management is by forming a marketing team specifically for marketing. By disseminating information about the development of tourism objects that occur in Malino Highland.